Performance Evaluation of an N₂ Membrane Generator under Different Operating Temperatures - Okttu Kristi Pradito; Agus Dwi Korawan; Drajat Indah Mawarni (Asosiasi Dosen Muda Indonesia, 2026)
Abstract: Nitrogen membrane generators have been commonly used for industrial applications owing to their simplicity and low operational costs, but the effect of operating temperature on the performance of membranes has not been well explored. Objectives: This study aims to evaluate the performance of a N₂ membrane generator with respect to nitrogen purity and nitrogen flow rate at different operating temperatures. Method: A quantitative experimental approach was employed by operating the membrane generator under controlled temperatures ranging from 35°C to 45°C. Performance data were analyzed using descriptive statistics and linear regression to identify temperature-performance relationships. Results: The results showed that nitrogen purity changed from 98.6% to 94.8% with increasing temperature, and nitrogen flow rate had increased from 18.2 Nm³/h to 23.7 Nm³/h with rise in temperature; and together these were emphasized by the regression analysis as significant effect for both parameters at p <0.05 and large R² values confirmed a very strong predictive relationship between them. Also, a threshold region at around 39°C was observed, beyond which N₂ purity decreases more quickly. Implications: The research emphasizes the need for effective thermal management in maximizing performance of membrane systems and provides practical insights into achieving optimal trade-offs between productivity and gas purity in industrial applications. Originality/Value: This study provides high resolution empirical evidence by employing very narrow 1°C temperature increments to yield detailed descriptions of temperature-dependent membrane behaviour, addressing the need for sophisticated models in application-oriented engineering.